2016
DOI: 10.1080/19440049.2016.1154613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen availability and pH on the furan concentration formed during thermal preservation of plant-based foods

Abstract: Effects of oxygen availability and pH on the furan formation during thermal 25 preservation of plant-based foods 26 Thermally treated fruit-and vegetable-based foods are important contributors to the furan exposure of 27 children and adults. Furan reduction by adding or removing precursors from the product has proven to 28 be challenging, because of major food constituents and interactions involved in the reaction pathways 29 leading to furan formation. Instead of intervening at the precursor level, it migh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…It should be noticed that the different reports are not always consistent (Märk et al., ). Reduction of the available amount of oxygen in food products (in potato purées supplemented with, respectively, ascorbic acid, fructose and poly‐unsaturated fatty acids; Palmers et al., ) or model systems (Märk et al., ) resulted in a variable decrease in the furan formation.…”
Section: Assessmentmentioning
confidence: 99%
“…It should be noticed that the different reports are not always consistent (Märk et al., ). Reduction of the available amount of oxygen in food products (in potato purées supplemented with, respectively, ascorbic acid, fructose and poly‐unsaturated fatty acids; Palmers et al., ) or model systems (Märk et al., ) resulted in a variable decrease in the furan formation.…”
Section: Assessmentmentioning
confidence: 99%
“…The carbon module labeling (CAMOLA) approach is frequently employed to explore specific reaction mechanisms (Schieberle, 2005). However, the results of factors impacting furan formation tend to differ and are even contradictory, as the furan generation from various precursors is influenced by the thermal intensity, oxygen availability, and pH of the investigated matrix (Palmers, Grauwet, Avenne et al., 2016). Understanding major furan formation routes during food processing are vital for its mitigation and safety control.…”
Section: Formation Pathways Of Furan In Foodsmentioning
confidence: 99%
“…A considerable furan reduction (70%−90%) was observed in vegetable and vegetable/meat baby foods sterilized using ohmic heating when compared with the traditional retort sterilization (Hradecky et al., 2017). Additionally, vacuum treatment also resulted in a remarkable reduction of furan in sterilized potato purées and high‐moisture foods such as meat sauce (Anese et al., 2014; Palmers, Grauwet, Avenne et al., 2016).…”
Section: Mitigation Measures Of Furan Exposurementioning
confidence: 99%
“…Furan, a heterocyclic compound composed of four carbons and one oxygen atom, is a lipid-soluble liquid with a low boiling point (32 °C) and high volatility. It has been well documented that furan and its derivatives are widely present in heated or processed foods. , Accordingly, furan derivatives can be divided into alkylated furans and oxygenated furans, with the former including 2-methylfuran, 3-methylfuran, 2-ethylfuran, 2,5-dimethylfuran, 2,3-dimethylfuran, 2-butylfuran, and 2-pentylfuran and the latter including furfural, furfuryl alcohol, and 2-acetylfuran. Of the various furan and its derivatives, furan and furfuryl alcohol were classified as Group 2B carcinogens (possibly carcinogenic to humans), while furfural was classified as Group 3 carcinogens (not classifiable as to its carcinogenicity to humans) according to the International Agency for Research on Cancer. , Thus, it is imperative to learn the variety and amount of furan and its derivatives in various commercial food products on the market.…”
Section: Introductionmentioning
confidence: 99%
“…studied the effect of roasting temperature on furan formation in coffee bean, and the furan levels were reported to be 22, 309, and 1792 ng/g following roasting at 150, 200, and 250 °C for 10 min, respectively. In a study dealing with the effect of oxygen availability on the furan content in thermally treated potato purees, the furan level was reduced by 60% under the condition of reduced oxygen and pH at 7 . Owczarek-Fendor, De Meulenaer further studied the effect of pH on furan formation in buffered starch-based systems containing various carbohydrates/sugar alcohols heated at 130 °C for 30 min and reported that a higher furan level was generated at pH 6 (4.55 ± 0.55 to 38.57 ± 1.34 ppb) than at pH 4 (1.59 ± 0.03 to 8.32 ± 0.84 ppb), probably caused by carbohydrate degradation and enol reaction at higher pH.…”
Section: Introductionmentioning
confidence: 99%